2017
DOI: 10.1371/journal.pone.0169575
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Mental Disorders in the Eastern Mediterranean Region, 1990-2013

Abstract: The Eastern Mediterranean Region (EMR) is witnessing an increase in chronic disorders, including mental illness. With ongoing unrest, this is expected to rise. This is the first study to quantify the burden of mental disorders in the EMR. We used data from the Global Burden of Disease study (GBD) 2013. DALYs (disability-adjusted life years) allow assessment of both premature mortality (years of life lost–YLLs) and nonfatal outcomes (years lived with disability–YLDs). DALYs are computed by adding YLLs and YLDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
122
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 67 publications
5
122
1
1
Order By: Relevance
“…Among the high-income countries in the EMR, mental disorders contributed to 2519 DALYS/100,000. Mental disorders rank as the ninth leading cause of disease burden in the EMR and the burden increased 11% from 1990 to 2013 12,13 . Depression and anxiety disorders are the most frequent mental disorders, and rates in women are up to double those in men 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the high-income countries in the EMR, mental disorders contributed to 2519 DALYS/100,000. Mental disorders rank as the ninth leading cause of disease burden in the EMR and the burden increased 11% from 1990 to 2013 12,13 . Depression and anxiety disorders are the most frequent mental disorders, and rates in women are up to double those in men 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this growth, Sharkey () reported that spending on mental health care represented only 0.34% of all healthcare expenditure, a rate that is seven times lower than spending in developed Western countries. This suboptimal level of spending on mental compared with physical health has been consistently observed across low‐, middle‐, and high‐income countries within the region (Charara et al, ; Okasha, Karam, & Okasha, ) and thus seems to reflect a bias against mental health rather than, say, the persistence of severe health problems affecting mortality, such as infectious diseases and malnourishment. Sharkey also noted that most of this spending within Qatar went on in‐patient services within the one mental health hospital situated in Doha, Qatar’s capital city.…”
Section: Introductionmentioning
confidence: 85%
“…Recent analysis from the global burden of disease data set has found that in Middle Eastern countries such as Qatar the burden from mental health disorders is higher than it is in other parts of the Western world (Charara et al, ). Furthermore, this burden has increased over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…The EMR is facing numerous health challenges as a result of previous wars, and recent revolutions and the wars that followed (Mokdad et al 2016; Charara et al 2017) resulted in a huge refugee problem with millions of refugees and massive consequences for the health and well-being of millions of displaced people. The EMR now carries the largest burden of displaced populations globally.…”
Section: Discussionmentioning
confidence: 99%